Education and Nationalism: giving parameters to the elementary school of Santa Catarina in Vargas Era - Santos, Ademir Valdir dos (2012)
This paper aims to present the project of nationalization for the scholar education. New sources of schools from 1930 to 1940 were analysed. We investigated the strategies used to form the Brazilian culture that tried to transform the German schools in Santa Catarina communities, using management and pedagogical practice to construct values and patriotic attitudes. The purpose of this research is to attempt reconfiguring the particular organization of scholar institutions which identity the State intended to eliminate and transform. The educational policies and educational practices aimed to develop the prescribed attitudes by nationalism, giving parameters by ethnic-cultural aspects to the historical process of the elementary school configuration.